X=−2 x=−1 x=1 6(0.5x−1.5)+2x=−9−(x+6) x = − 2 – 6 ( 0.5 x − 1.5 ) + 2 x = − 9 − ( x + 6 ) x = − 1 – 6 ( 0.5 x − 1.5 ) + 2 x = − 9 − ( x + 6 ) x = 1 – 6 ( 0.5 x − 1.5 ) + 2 x = − 9 − ( x + 6 ) 4(0.5x−2)+3x=−14−(x+6) x = − 2 – 4 ( 0.5 x − 2 ) + 3 x = − 14 − ( x + 6 ) x = − 1 – 4 ( 0.5 x − 2 ) + 3 x = − 14 − ( x + 6 ) x = 1 – 4 ( 0.5 x − 2 ) + 3 x = − 14 − ( x + 6 ) 8(0.5x−3)+4x=−9−(x+6)

Respuesta :

Given:

Three equations are

[tex]6(0.5x-1.5)+2x=-9-(x+6)[/tex]

[tex]4(0.5x-2)+3x=-14-(x+6)[/tex]

[tex]8(0.5x-3)+4x=-9-(x+6)[/tex]

Three solutions are [tex]x=-2,x=-1,x=1[/tex].

To find:

The solution of each equation from the given solutions.

Solution:

We have,

[tex]6(0.5x-1.5)+2x=-9-(x+6)[/tex]

Using distributive property, we get

[tex]3x-9+2x=-9-x-6[/tex]

[tex]5x-9=-15-x[/tex]

Isolate variable terms.

[tex]5x+x=-15+9[/tex]

[tex]6x=-6[/tex]

Divide both sides by 6.

[tex]x=-1[/tex]

Similarly,

[tex]4(0.5x-2)+3x=-14-(x+6)[/tex]

[tex]2x-8+3x=-14-x-6[/tex]

[tex]5x-8=-20-x[/tex]

[tex]5x+x=-20+8[/tex]

[tex]6x=-12[/tex]

[tex]x=-2[/tex]

Now,

[tex]8(0.5x-3)+4x=-9-(x+6)[/tex]

[tex]4x-24+4x=-9-x-6[/tex]

[tex]8x-24=-15-x[/tex]

[tex]8x+x=-15+24[/tex]

[tex]9x=9[/tex]

[tex]x=1[/tex]

Therefore, the solutions of given equations [tex]6(0.5x-1.5)+2x=-9-(x+6)[/tex], [tex]4(0.5x-2)+3x=-14-(x+6)[/tex] and [tex]8(0.5x-3)+4x=-9-(x+6)[/tex] are x=-1, x=-2 and x=1 respectively.

ACCESS MORE